Circ_0087862 promotes the progression of colorectal cancer by sponging miR‐142‐3p and up‐regulating BACH1 expression. Issue 12 (13th August 2021) - Huang, Bo; Cui, De‐Jun; Yan, Fang; Yang, Liu‐Chan; Zhang, Man‐Man; Zhao, Xun
Abstract: Circular RNAs (circRNAs) feature prominently in regulating the malignant biological behaviors of colorectal cancer (CRC), including cell viability, cell cycle progression, apoptosis, migration, invasion, and so on. This study is performed to probe into the biological function and molecular mechanism of circ_0087862 in CRC. The expression profile of GSE138589 was available from Gene Expression Omnibus (GEO), and the differentially expressed circRNAs were analyzed by GEO2R. The expression of circ_0087862, miR‐142‐3p, and BACH1 mRNA in CRC tissues and cells was measured by qRT‐PCR. CCK‐8 assay was employed to determine the proliferation of CRC cells. Scratch wound healing and transwell assays were used to examine the migration and invasion of CRC cells. The targeting relationships between circ_0087862 and miR‐142‐3p, and between miR‐142‐3p and BACH1 3′UTR were verified by dual‐luciferase reporter gene assay and RIP assay. BACH1 protein expression was probed by western blot. Circ_0087862 was highly expressed in CRC tissues and cell lines. Knocking down circ_0087862 significantly restrained the multiplication, migration and invasion of CRC cells. miR‐142‐3p inhibition weakened the impact of circ_0087862 knockdown on CRC cells. Circ_0087862 regulated BACH1 expressions by targeting miR‐142‐3p. Circ_0087862 regulates BACH1 expressions through sponging miR‐142‐3p, and promotes the proliferation, migration, and invasion of CRC cells.